An evaluation of primary immunization coverage among 12-23 months old children in an urban area of Western Maharashtra: A community-based study - Jatti, G M; Bandichhode, S T; Nandimath, V A; Jadhav, S B (Indian Journal of Child Health, 2016)
Introduction: Immunization is a process whereby a person is made immune to infectious diseases. In 1985, Universal Immunization Programme started in India with the aim of achieving at least 85% coverage of primary immunization. A child is considered fully immunized if he/she received one dose each of Bacille Calmette-Guérin and measles and three doses of oral polio vaccine, hepatitis B virus, and DPT before the age of 1 year. Objectives: To determine primary immunization coverage among 12-23 months old children and the factors affecting primary immunization coverage. Materials and Methods: A cross-sectional community-based study conducted from March 2011 to June 2011 in Miraj city of Maharashtra. The WHO 30 by 7 cluster sampling technique was used to collect data from 210 study subjects. Results: Among 210 (100%) children, 127 (60.5%) children were fully immunized while remaining 83 (39.5%) were partially immunized or unimmunized. Negligence of parents toward immunization was the main reason for incomplete immunization status of children. Conclusion: Health education activities for parents, especially in mothers, emphasizing the importance and need of immunization of children at right time could be arranged in communities. Equitable, participatory and intersectoral approach is need of hour for health care of children.